Diagnostic error: what Muir-Torre syndrome has taught us - Wall, Dmitri (BMJ Case Rep, 2015)
A low-grade sebaceous carcinoma was excised from a 55-year-old woman's neck. At follow-up, 11 months later, a recent diagnosis of mucinous adenocarcinoma of the colon and history of clear cell endometrial carcinoma were identified. A strong family history of bowel cancer suggested Muir-Torre syndrome. Unexpectedly, hereditary non-polyposis colorectal cancer had previously been genetically confirmed; the results were found loosely filed in the paper chart. The patient had not informed us about her diagnosis; having discussed the case with other physicians she felt the diagnosis would be common knowledge. In 1999, US National Institute of Medicine estimated that preventable medical error resulted in the deaths of 44–98 000 people yearly in US hospitals. Four categories of medical error, including diagnosis, treatment, preventive and ‘other’ were described, while the reasoning processes that result in these errors are outlined by Reason et al. We utilise this rare case to illustrate these important concepts.